2015
DOI: 10.1016/j.jneuroling.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the language input affects brain activation during learning from a natural language

Abstract: Artificial language studies have demonstrated that learners are able to segment individual word-like units from running speech using the transitional probability information. However, this skill has rarely been examined in the context of natural languages, where stimulus parameters can be quite different. In this study, two groups of English-speaking learners were exposed to Norwegian sentences over the course of three fMRI scans. One group was provided with input in which transitional probabilities predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 76 publications
10
53
1
Order By: Relevance
“…Studies also report striatal activation in SL [56,57], with activity in the caudate body predicting discrimination of statistically predictable versus unpredictable transitions in visual and auditory SL [14,57].…”
Section: Candidate Memory Systems For Statistical Learningmentioning
confidence: 99%
“…Studies also report striatal activation in SL [56,57], with activity in the caudate body predicting discrimination of statistically predictable versus unpredictable transitions in visual and auditory SL [14,57].…”
Section: Candidate Memory Systems For Statistical Learningmentioning
confidence: 99%
“…The present results can be compared directly with the results of our previous word segmentation study (Plante et al, 2015), in that the procedures for scanning and ICA analyses were identical. In that word segmentation study, activation in the pars opercularis was reported in the left hemisphere for two ICs and in the right hemisphere for four ICs.…”
Section: Discussionmentioning
confidence: 71%
“…However, activation in this area and others (e.g., frontal regions, and areas in the temporo-parietal-occipital junction) is not consistently evident across or within word segmentation studies (Plante et al, 2015). For example, two studies (McNealy et al, 2006; Karuza et al, 2013) reported activation in this area not during exposure, but in relation to performance on a post-scan test.…”
Section: Introductionmentioning
confidence: 99%
“…For most infants, simply exposing them to a language guarantees that they will learn the language. Regardless of nationality, infants are natural language learners and are generally born with the ability to utter all of the sounds that humans are capable of producing [17][18][19][20][21]. After some time in a particular language environment, the infant will stop producing some sounds in favor of those that he or she is consistently hearing.…”
Section: Speech Acquisition and Learning To Readmentioning
confidence: 99%